Intratumoral androgen levels are linked to TMPRSS2-ERG fusion in prostate cancer. Issue 9 (September 2018) - Knuuttila, Matias; Mehmood, Arfa; Mäki-Jouppila, Jenni; Ryberg, Henrik; Taimen, Pekka; Knaapila, Juha; Ettala, Otto; Boström, Peter J; Ohlsson, Claes; Venäläinen, Mikko S; Laiho, Asta; Elo, Laura L; et al.
Abstract : Intratumoral androgen biosynthesis is one of the mechanisms involved in the progression of prostate cancer, and an important target for novel prostate cancer therapies. Using gas chromatography-tandem mass spectrometry and genome-wide RNA sequencing, we have analyzed androgen concentrations and androgen-regulated gene expression in cancerous and morphologically benign prostate tissue specimens and serum samples obtained from 48 primary prostate cancer patients. Intratumoral dihydrotestosterone (DHT) concentrations were significantly higher in the cancerous tissues compared to benign prostate ( P  < 0.001). The tissue/serum ratios of androgens were highly variable between the patients, indicating individual patterns of androgen metabolism and/or uptake of androgens within the prostate tissue. An unsupervised hierarchical clustering analysis of intratissue androgen concentrations indicated that transmembrane protease, serine 2/ETS-related gene (TMPRSS2-ERG)-positive patients have different androgen profiles compared to TMPRSS2-ERG-negative patients. TMPRSS2-ERG gene fusion status was also associated with an enhanced androgen-regulated gene expression, along with altered intratumoral androgen metabolism, demonstrated by reduced testosterone concentrations and increased DHT/testosterone ratios in TMPRSS2-ERG-positive tumors. TMPRSS2-ERG-positive and -negative prostate cancer specimens have distinct intratumoral androgen profiles, possibly due to activation of testosterone-independent DHT biosynthesis via the alternative pathway in TMPRSS2-ERG-positive tumors. Thus, patients with TMPRSS2-ERG-positive prostate cancer may benefit from novel inhibitors targeting the alternative DHT biosynthesis.